The price of one bag of popcorn is $3.75
Step-by-step explanation:
Let,
x represent the cost of a bag of popcorn
y represent the cost of a drink.
According to given statement;
4x+12y=30 Eqn 1
x+6y=11.25 Eqn 2
Multplying Eqn 2 by 2
![2(x+6y=11.25)\\2x+12y=22.50\ \ \ Eqn\ 3](https://tex.z-dn.net/?f=2%28x%2B6y%3D11.25%29%5C%5C2x%2B12y%3D22.50%5C%20%5C%20%5C%20Eqn%5C%203)
Subtracting Eqn 3 from Eqn 1
![(4x+12y)-(2x+12y)=30-22.50\\4x+12y-2x-12y=7.50\\2x=7.50](https://tex.z-dn.net/?f=%284x%2B12y%29-%282x%2B12y%29%3D30-22.50%5C%5C4x%2B12y-2x-12y%3D7.50%5C%5C2x%3D7.50)
Dividing both sides by 2
![\frac{2x}{2}=\frac{7.50}{2}\\x=3.75](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3D%5Cfrac%7B7.50%7D%7B2%7D%5C%5Cx%3D3.75)
4x+12y=30 and x+6y=11.25 can be used to find the price of one bag of popcorn and the price of one drink.
The price of one bag of popcorn is $3.75
Keywords: linear equation, elimination method
Learn more about elimination method at:
#LearnwithBrainly
Answer:
what are we actually solving for?....
anyways I had a suggestion ion know if it's right or wrong....
<em>Isolate</em><em> </em><em>the</em><em> </em><em>variable</em><em> </em><em>by</em><em> </em><em>diving</em><em> </em><em>each</em><em> </em><em>side</em><em> </em><em>by</em><em> </em><em>factor</em><em> </em><em>that</em><em> </em><em>don't</em><em> </em><em>contain</em><em> </em><em>the</em><em> </em><em>vari</em><em>able</em><em>.</em>
<em>Therefore</em><em> </em><em>x</em><em>=</em><em>7</em><em>.</em><em>2</em>
Answer:
WHAT UP
Step-by-step explanation:
DO THIS AND THAT LOL
Answer:
6
Step-by-step explanation:
Answer:
A. 36
Step-by-step explanation:
Because the two angles at the bottom of both the triangles are congruent, the two triangles are similar. Therefore, the corresponding side lengths of the triangles must be proportional to each other
if the area of a triangle is hb/2,
(with h=length of height, b=length of base)
the height of the first triangle is:
25 = 10h/2
50 = 10h
h=5
you can write ratios representing the proportions of the two triangles:
5/x = 10/12 (with x=height of second triangle)
x=6
then find the area of the second triangle with the height (6) and base (12)
(6*12)/2 = 36